Konstruksi Kewenangan dalam Perjanjian Korporasi: Dialektika Keabsahan Formal dan Keadilan Substantif dalam Perspektif Kelsen dan Rahardjo - Chandra, William; Silalahi, Wilma (APPS Publications, 2025)
This study aims to analyze the construction of contractual authority in corporate law from a theoretical perspective, particularly by examining the tension between Hans Kelsen’s Pure Theory of Law and Satjipto Rahardjo’s Progressive Legal Theory. The central research question explores how formal legality and substantive justice interact in validating corporate contracts, especially in cases involving unauthorized representation. This study adopts a normative juridical approach, relying on primary legal sources such as the Indonesian Civil Code and Company Law, and theoretical literature from Kelsen and Rahardjo. The analysis is conducted qualitatively through conceptual, systematic, and comparative methods, focusing on reconstructing the notion of authority in corporate contracts. The findings reveal that Kelsen’s theory mandates strict normative delegation for legal validity, while Rahardjo’s approach allows for the recognition of good faith and implied authority when aligned with justice and fairness. Through this dialectic, the study demonstrates how corporate law can incorporate both normative order and commercial adaptability, as reflected in Indonesian jurisprudence and comparative doctrines like apparent authority and indoor management. This study contributes a theoretical synthesis that bridges rigid normativism with contextual legal realism. It offers a new conceptual framework for interpreting ultra vires acts and corporate liability, encouraging a shift toward more responsive and inclusive legal interpretations in modern business law.